Primary and isolated cutaneous precursor B‐lymphoblastic lymphoma in an infant. Issue 3 (18th March 2021) - Jouini, Raja; Chabchoub, Ines; Khanchel, Fatma; Helal, Imen; Badri, Talel; Ben Brahim, Ehsene; Hammami, Houda; Chadli‐Debbiche, Ashraf
Abstract: Cutaneous lesions may represent the initial sign of various neoplasms in children, including histiocytosis, neuroblastomas, and lymphomas. Primary cutaneous lymphoblastic lymphomas are rare and involve mostly the B‐cell phenotype. Herein, we report a case of isolated, primary B‐lymphoblastic lymphoma in a 7‐month‐old infant and emphasize the importance of early diagnosis.